(3GdEaGOI aj Gdabg Ydi ePgH GdeDjO HGddg CMeO Hf GdMSjf GdgGQhfis - (3CHh GdbGSe GdMSjf Hf GdMSjf GdghSej GdeDjOjs
(3ChdgG (B:s
(3Chdg HYO GdHSedI HOGAkG HcJGH GdWgGQI , HGH GdejGg s
(3BNQgG (B:s
(3BNQg ef aUd ai GdJhHI (B" (3bhdg (B:(3hef de jQV Gddg Yfg , adG jLhR Ef QVi Yfg NUeGg Je GdcJGH HMeO Gddg hefg s
(3cJHJ GdYfhGfGJ HNW eLhOs
(3cJH HYVgG HGdMeQIs
(3hHBNQgG HebOGQ hQbI EVGaI SGbWI ef cJGH GdHjhYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis